Assessment of Cervical Cancer Prevention and Treatment Infrastructure in Belize. (2021) - Neibart, Shane S.; Smith, Tiffany A.; Fang, Jennifer H.; Anderson, Taylor; Kulkarni, Abha; Tsui, Jennifer; Hudson, Shawna V.; Peck, Gregory L.; Hanna, Joseph S.; Beer, Natalia Largaespada; Einstein, Mark H.
Abstract : PURPOSE: Belize has one of the highest cervical cancer burdens among Latin American and Caribbean countries, despite the implementation of national policies to increase access to prevention and treatment services. This study evaluates the policies, infrastructure, and workforce of the cervical cancer management system in Belize to inform capacity building efforts. METHODS: In 2018, health facility assessments were conducted across all six districts of Belize at the national pathology facility and 12 public facilities identified as critical to cervical cancer control. Human and infrastructure resource availability and existing policies related to cervical cancer screening and treatment services were assessed through a structured instrument. RESULTS: The public cervical cancer screening workforce in Belize consists of 75 primary care nurses and physicians—one per 1, 076 screening-eligible women, with 44% conducting rural outreach. All districts have at least one screening facility, but 50% perform screening services only once per week. Colposcopy and loop electrical excision procedures are available in three and four districts, respectively; radical hysterectomy and chemotherapy are available in two districts; and radiation therapy is unavailable. Of essential pathology equipment, 38.5% were present and functional, 23% were present but nonfunctional, and 38.5% were unavailable. Additionally, 35% of supplies were unavailable at the time of assessment, and 75% were unavailable at least once in the 12 months before assessment. CONCLUSION: Public-sector cervical cancer management services differ among districts of Belize, with tertiary service availability concentrated in the largest district. Screening, outreach, and pathology are limited mostly by resource availability. This study characterizes the current capacity of services in Belize and pinpoints health system components for future investment and capacity-building efforts.